Rút gọn biểu thức:
\(A=\frac{\sqrt{2.\sqrt[4]{8}-2\sqrt{\sqrt{2}+1}}}{\sqrt{\sqrt[4]{8}+\sqrt{\sqrt{2}-1}}-\sqrt{\sqrt[4]{8}-\sqrt{\sqrt{2}-1}}}\)
\(B=\frac{\sqrt{\sqrt[4]{27}+\sqrt{\sqrt{3}-1}}-\sqrt{\sqrt[4]{27}-\sqrt{\sqrt{3}-1}}}{\sqrt{2.\sqrt[4]{27}-2\sqrt{2\sqrt{3}+1}}}\)
\(A^2=\frac{2\sqrt[4]{8}-2\sqrt{\sqrt{2}+1}}{2\sqrt[4]{8}-2\sqrt{\sqrt[4]{8}^2-\sqrt{\sqrt{2}+1}^2}}\)
biến đổi được \(\sqrt[4]{8}^2-\sqrt{\sqrt{2}+1}^2=\sqrt[4]{64}-\sqrt{2}+1=\sqrt[4]{2^4.\sqrt{2}^4}-\sqrt{2}+1=2\sqrt{2}-\sqrt{2}+1=\sqrt{2}+1\)
Suy ra A = 1
Nghĩa ơi:v Không hiểu từ sau cái chữ: "Biến đổi" á